92.5k views
0 votes
Please help me .

Select the correct answer.
Which expression is equivalent to the given expression?
2.12 – 111 – 6
A. (2x + 3)(3-2)
B. 2(x + 3)(x - 2)
C. (2 + 1) (1 - 6)
D. 2(1 – 3)(x + 1)

Please help me . Select the correct answer. Which expression is equivalent to the-example-1
User Jobima
by
6.1k points

1 Answer

1 vote

Answer:

(2x + 3)(x - 2)

Explanation:

use FOIL

First, Outside, Inside, Last

2x x x = 2x²

2x x -2 = -4x

3 x x = 3x

3 x -2 = -6

2x² - 4x + 3x - 6

User Shibley
by
5.7k points